The cost and distributive impact of the informality incentives from non-contributory spending: the cases of AUH in Argentina and AFAM-PE in Uruguay - Alaimo, Verónica (2018)
Since the last decade most countries in Latin America have experienced substantial changes in their social policies implementing a set of non-contributory social assistance benefit programs. There is a permanent debate from the policy makers and academics about the direct and indirect labor market effects of these programs. The most concerning discussion in the region is the unintended incentive towards informality that these policies could generate. This paper estimates the fiscal cost and distributive impact of this labor distortion conducted by the two main non-contributory programs in Argentina and Uruguay: Asignación Universal por Hijo (AUH) and Asignaciones Familiares – Plan de Equidad (AFAM-PE), respectively. We find that the substitution effect from formal to informal employment attributed to each program represents a relevant portion of the total budget of these policies. The results also reflect that a simple fiscal incidence analysis of these programs that ignore the consequences of these labor incentives on the market income distribution will exaggerate the true effect of these policies on the disposable or final income poverty and inequality.